Possible Paraneoplastic Amyotrophic Lateral Sclerosis Presenting as Respiratory Failure in a Breast Cancer Patient: A Case Report - Maryam Albaji; Khashayar Ashkboos; Kosar Bagherzadeh (Clinical Case Reports, 2026)
ABSTRACT A 63‐year‐old female with metastatic breast cancer presented with acute hypercapnic respiratory failure secondary to severe diaphragmatic dysfunction and mixed upper and lower motor neuron signs. Serum onconeural and neural surface antibody panels were negative, and initial cerebrospinal fluid analysis revealed albuminocytologic dissociation. Immunotherapy with intravenous immunoglobulin (IVIG) produced no clinical improvement, necessitating invasive mechanical ventilation and gastrostomy. Applying the 2021 PNS‐Care consensus criteria, the case fulfills criteria for possible paraneoplastic amyotrophic lateral sclerosis (ALS), although coincidental sporadic disease cannot be excluded. A markedly elevated erythrocyte sedimentation rate (ESR) was observed, largely attributable to skeletal metastases and localized pulmonary collapse. Clinicians must maintain a high index of suspicion for motor neuron disease in cancer patients with unexplained hypoventilation.